The Development of Engineering Qualifications in Ukraine and China Through the Prism of Experience, Transformations in the Educational Space, Personnel Policy, and the Integration of Dual Learning Models - Chao, Shao; Kharchenko, Svitlana; Yue, Cao; Zheng, Gao; Li, Zhang (European Journal of Sustainable Development, 2025)
In this article, we will look at how engineering qualifications are developed in the country of Ukraine in context of international comparison with much interest in the experience of China in terms of establishing a dual education system and digitalization strategies. The study design includes qualitative content analysis of Ukrainian policy texts and a systematic empirical survey, which will be completed at the beginning of 2025 with the help of students and instructors of vocational and technical learning facilities. The research explores the issue of introducing dual education, digital technologies (including AI, VR, AI) and public-private partnerships to the engineering training system in Ukraine, determining its limitations of structure, division of power, and regional inequality, mainly between urban and rural institutions. To accomplish the purpose of the analysis, the strategic coherent of the vocational education reforms in China is confirmed and compared to the experimental and decentralized reforms in Ukraine. There is a particular focus on trainings and professional development of teachers in the digital innovation, capacity-building of institutions and lack of nationwide performance indicators in Ukraine. These results contribute to the possible usefulness of hybrid governance systems that would intertwine Chinese strategic planning with the flexibility of the Ukrainian model that will allow flexible routes of reforms without compromising the ability to coordinate at the national level or meet international standards. The article ends with some policy innovation and future research recommendations in transition economies that are faced with a lot of complicated transformations in both education and the labor market. Keywords: education, dual education, vocational education, dual system, engineering training, China, Ukraine, digitalization, public-private partnership, education policy, innovative economy, human resource development.